Robust Singular Value Decomposition Algorithm for Unique Faces - Patel, Ibrahim; Kulkarni, Raghavendra; Rao, Dr.P. Nageswar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
It has been read and also seen by physical encounters that there found to be seven near resembling humans by appearance .Many a times one becomes confused with respect to identification ofÂ such near resembling faces when one encounters them. TheÂ recognitionÂ ofÂ familiarÂ facesÂ playsÂ aÂ fundamentalÂ roleÂ inÂ ourÂ social interactions. HumansÂ areÂ ableÂ toÂ identifyÂ reliablyÂ aÂ largeÂ numberÂ ofÂ facesÂ and psychologistsÂ areÂ interestedÂ inÂ understandingÂ theÂ perceptualÂ andÂ cognitive mechanismsÂ atÂ theÂ baseÂ ofÂ theÂ faceÂ recognitionÂ process. As it is needed that an automated face recognition system should be faces specific, it should effectively use features that discriminate a face from others by preferably amplifying distinctive characteristics of face. Face recognition has drawn wide attention from researchers in areas of machine learning, computer vision, pattern recognition, neural networks, access control, information security, law enforcement and surveillance, smart cards etc. The paper shows that the most resembling faces can be recognized by having a unique value per face under different variations. Certain image transformations, such as intensity negation, strange viewpoint changes,Â andÂ changesÂ inÂ lightingÂ directionÂ canÂ severelyÂ disruptÂ humanÂ face recognition. It has been said again and again by research scholars that SVD algorithm is not good enough to classify faces under large variations but this paper proves that the SVD algorithm is most robust algorithm and can be proved effective in identifying faces under large variations as applicable to unique faces. This paper works on these aspects and tries to recognize the unique faces by applying optimized SVD algorithm.